2019
DOI: 10.1371/journal.pcbi.1007330
|View full text |Cite
|
Sign up to set email alerts
|

Weak coupling between intracellular feedback loops explains dissociation of clock gene dynamics

Abstract: Circadian rhythms are generated by interlocked transcriptional-translational negative feedback loops (TTFLs), the molecular process implemented within a cell. The contributions, weighting and balancing between the multiple feedback loops remain debated. Dissociated, free-running dynamics in the expression of distinct clock genes has been described in recent experimental studies that applied various perturbations such as slice preparations, light pulses, jet-lag, and culture medium exchange. In this paper, we p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…We found that the oscillation period strongly depended on the degradation rates of REVERB, E4BP4 and DBP (figure 10). Since the period of the ODE models was approximately 20 h [57], we tuned the degradation rate of REVERB (γ REV ) to set the period to approximately 24 h. Simulations of the three DDE model with the published parameter set yielded 24 h oscillations [31]. The time series solutions of the eight ODE and three DDE models are shown in figure 3.…”
Section: Different Circadian Clock Models Exhibit Self-sustained Oscimentioning
confidence: 99%
See 3 more Smart Citations
“…We found that the oscillation period strongly depended on the degradation rates of REVERB, E4BP4 and DBP (figure 10). Since the period of the ODE models was approximately 20 h [57], we tuned the degradation rate of REVERB (γ REV ) to set the period to approximately 24 h. Simulations of the three DDE model with the published parameter set yielded 24 h oscillations [31]. The time series solutions of the eight ODE and three DDE models are shown in figure 3.…”
Section: Different Circadian Clock Models Exhibit Self-sustained Oscimentioning
confidence: 99%
“…To investigate whether nonlinear phenomena appear in the mammalian molecular clock, we analysed two recent models of the mammalian circadian clockwork published by Almeida et al [57] and Schmal et al [31]. The model equations are shown in figures 7 and 8.…”
Section: Appendix a Equations For The Eight Ode And Three Dde Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…While parameter dependencies of oscillator properties such as the amplitude or free-running period are usually intertwined in complex molecular models, the Poincaré oscillator (1, 2) conveniently treats these features as independent parameters. Thus, the impact of internal clock parameters on entrainment and synchronization properties can be studied in a straightforward manner as demonstrated in several studies (Abraham et al, 2010;Granada et al, 2013;Gu et al, 2014;Tokuda et al, 2015;Myung et al, 2018;Schmal et al, 2019). In the following we will represent the circadian clock of an organism by a Poincaré oscillator (1, 2) and study its entrainment under natural light environments, using a simple celestial mechanics derivation.…”
Section: The Poincaré Oscillator: a Conceptual Model For Limit Cycle mentioning
confidence: 99%